Trainee Accountants’ Perceptions of the Current State of the Accountancy Profession in South Africa and their Responses Based on the EVLN Model: Array - Ndlovu, Jane; Yasseen, Yaeesh; Brahmbhatt, Yogesh (The Journal of Accounting and Management, 2020)
This article investigates the current state of the accountancy profession in South Africa in light of the recent accounting scandals and how these negative perceptions impact the response of Trainee Accountants’ (TAs). An anonymous questionnaire was directed to TAs affiliated with two local professional accounting organisations. Results were generalised using descriptive statistics which followed a deductive approach. Findings suggest that majority of TAs were influenced by the current state of the profession. These recent scandals have created negative perceptions of the profession as TAs indicated that these reports make them ‘pessimistic’. Analysis of the EVLN (Exit, Voice, Loyalty and Neglect) employee behavioural response model suggests that TAs with negative perceptions were more inclined to demonstrating E and V rather than L and N.